Multiple Factors Affecting Length of Hospital Postpartal Care in Eclampsia Patients - Gita Dianty (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To identify any factors that could cause longer care at hospitals in eclampsia patients. Methods: It was a retrospective, cross sectional study design and conducted in Dr. Mohammad Hoesin Hospital Palembang from January 2005 to December 2009. This research conducted in 176 samples divided into 2 groups namely short-stay group (1-5 days) with 92 patients and longer stay group (≥ 5 days) with 87 patients, with mean length of hospital stay 5.41±3.43 days. Results: The most common mode of delivery in the group who stayed ≥ 5 days was cesarean section (44.8%), while the most common delivery route in the group who stayed < 5 days was forceps extraction (43.5%). The mean thrombocytes count in the longer stay group was lower than in the short-stay group (213459.77±108391.81 vs 258945.65±92213.24 mm3), which was significantly different (p=0.003). Ureum and LDH concentration in longer stay group was higher, and statistic test was found to be significantly different (p<0.05), while renal failure complication was mostly experienced by the longer stay group (20.7%). Conclusions: Thrombocytes count, LDH, acute renal failure and ICU has significant difference and greater in postpartal eclampsia group that is longer treated. [Indones J Obstet Gynecol 2012; 36-2: 75-80] Keywords: complication, eclampsia, length of hospital stay